Implementation of Mitigation Overcoming Annual Flood Disasters in Demak Regency - Faizal Aco (Journal of Social and Policy Issues, 2025)
Most areas near the sea are highly vulnerable to flooding, both flash floods and flooding during heavy rains. When a natural disaster occurs, the most important thing to consider is disaster management and control. Post-flood disaster management is crucial to mitigate the impact and damage caused to victims, as well as the illnesses they suffer. Rapid preparation is crucial to reduce risk, damage, and impact. Government policy is a crucial component in assisting flood victims. A qualitative descriptive research approach was used in this study. To improve the accuracy of the research objectives and provide a clear picture of the phenomena or social realities studied, a qualitative descriptive study was chosen. A qualitative approach was used to collect descriptive data that can provide a detailed picture of disaster mitigation, such as prevention, mitigation, emergency response, and recovery. Direct interviews were used to obtain information related to disaster mitigation in overcoming the impact of flooding in Karanganyar Regency and Demak Regency with several informants, such as the Demak Regency Regional Disaster Management Agency (BPBD), the Karanganyar Regency Government, and the Village Government. Significant prevention through environmental and physical regulation and control. River normalization, such as river deepening and dredging, and river widening to restore strength. Meanwhile, work on the breached embankment is still incomplete. The Karanganyar Regency Government is working to prevent flooding by normalizing the river, such as deepening and dredging, and widening it to restore its strength.